Impact of supplementary nutrition on the nutritional status of children below six years of age registered under ICDS in Gandhinagar - Chavada, Mallika V.; Prajapati, Jagruti D.; Macwana, Jayprakash; Oza, Jaydip R.; Patel, Twinkle R.; Prajapati, Drashtant R. (International Journal Of Community Medicine And Public Health, 2022)
Background: Under nutrition has significant impact on morbidity and mortality of the children of age group 0-6 years. ICDS is working to combat under nutrition of these children since many years by providing supplementary nutrition. Objective of this study is to determine the progress in the nutritional status of the children of age group 0-6 years registered under ICDS who are taking benefit of supplementary nutrition from anganwadi. Methods: To determine the progress in the nutritional status of the children of age group 0-6 years registered under ICDS who are taking benefit of supplementary nutrition from anganwadi. Results: A cross sectional study was conducted at anganwadi centers under field practice area of urban health and training centre, Sector -24, GMERS Medical College, Gandhinagar in the month of November and December 2019. Total 200 children fit to inclusion and exclusion criteria were enrolled from 3 anganwadi centre. The structured baseline questionnaire was used to include basic socio-demographic detail, detail of anthropometry measurement and regularity in attendance etc. WHO growth chart V 3.2.2 was used to calculate the Z score for the weight for height (wasting), weight for age (underweight) and height for age (stunting). Conclusions: High prevalence of Stunting and wasting in anganwadi children is alarming as may have overall developmental effect in future. Engagement of community and family members and focus on other socio demographic risk factors from childhood malnutrition is need of the ICDS program.